Long-Term Outcome of Rescue Stenting for Acute Intracranial Atherosclerotic Stenosis Related Large Vessel Occlusion in Anterior Circulation - Park, Hyungjong; Kim, Byung Moon; Kim, Jun-Whee; Kim, Jin Woo; Baek, Jang-Hyun; Kim, Dong Joon; Kim, Min Jeoung; Yoon, Sun; Jang, Chang Ki; Kim, Sunghan; Heo, JoonNyung; Lee, Jung-Keun; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Rescue stent (RS) is an accepted rescue option after failed mechanical thrombectomy (MT) for acute ischemic stroke due to intracranial atherosclerotic stenosis (ICAS)-related large vessel occlusion (LVO). However, the long-term outcomes (≥ 12 months) of RS have not yet been elucidated.MATERIALS AND METHODS: We retrospectively analyzed the data of 154 patients with RS for ICAS-related LVO, which were identified from prospectively maintained multicenter database of RS after MT failure, to assess good outcome (mRS 0–2), mortality, stroke recurrence, symptomatic intracranial hemorrhage (SICH) and stent patency.RESULTS: Among 154 patients, successful recanalization was achieved in 132 (85.7%) after RS. Clinical follow-up was available in 148 patients at 3 months, of whom 126 were followed longer than 12 months. Good outcome was observed in 53.4% (79/148) at 3 months and 53.2% (67/126) at the final assessment among survivors (median [interquartile range (IQR)] months, 33 [13-91]). The overall incidence of mortality was 16.2% (24/148) Mortality occurred in 8.8% (13/148) of patients at 3 months and 8.7% (11/126) thereafter, respectively. Stroke recurrence was 0.7% (1/148) within 3 months and 3.2% (4/126) thereafter. The overall incidence of SICH was 9.5% (14/148). SICH occurred in 8.8% (13/148) within the first 3 months, and in 0.8% (1/126) thereafter. The stented vessel was patent in 81.1% (99/122) at the first follow-up (median [IQR] days, 3 [1-125]) and 96.7% (89/92) at the final follow-up (median [IQR] months, 18 [13-68]).CONCLUSIONS: Patients with RS for ICAS-LVO showed a low stroke recurrence rate in the long term. The long-term patency of rescue stent appears to remain durable, particularly when it remains patent during the initial follow-upABBREVIATIONS: ICAS = intracranial atherosclerotic stenosis; LVO = large vessel occlusion; AIS = acute ischemic stroke; MT = mechanical thrombectomy; RS = rescue stenting; CT = computed tomography; MR = magnetic resonance; MMD = moyamoya disease; Intra-arterial = IA; Intravenous = IV; DAPT = dual antiplatelet therapy.